Voltage regulator modeling for the three-phase power flow in distribution networks - Gallego, L. A. [UNESP]; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
In this paper a three-phase power flow for electrical distribution systems considering different models of voltage regulators is presented. A voltage regulator (VR) is an equipment that maintains the voltage level in a predefined value in a distribution line in spite of the load variations within its nominal power. Three different types of connections are analyzed: 1) wye-connected regulators, 2) open delta-connected regulators and 3) closed delta-connected regulators. To calculate the power flow, the three-phase backward/forward sweep algorithm is used. The methodology is tested on the IEEE 34 bus distribution system. ©2008 IEEE.
Keywords: Distribution systems; Three-phase power flow; Voltage regulators; Distribution lines; Distribution network; Electrical distribution system; Load variations; Power flows; Sweep algorithms; Voltage levels; Distributed parameter networks; Distribution of goods; Local area networks; Voltage control; Voltage stabilizing circuits; Electric potential